Customer Loyalty is Influenced by Experience Quality With Moderating Currency and Conversation and Co-Creation Roles - Surya Bintarti; Inge Nur Oktavia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The COVID-19 virus in 2020 became an event that affected the world. The government restricts people's activities by closing the film industry, streaming services known as Video on demand (VOD) are increasing such as the WeTV application to watch movies online. The purpose of this study is to examine customer loyalty influenced by experience quality with moderation of currency and the role of conversation and co-creation in the WeTV application. Respondents of this study were 112 who had used the WeTV application in Bekasi Regency. Nonprobability sampling of this population with purposive method. Conversation is able to drive Experience quality; Co-creation is able to drive Experience quality; Conversation has not been able to moderate Currency on Experience quality; Co-creation is able to moderate Currency on Experience quality; Experience quality is able to drive Customer loyalty; Conversation has not been able to mediate Experience quality on Customer Loyalty; Co-creation is able to mediate Experience quality on Customer loyalty.